An empirical analysis of factors affecting the commercial adoption of autonomous trucks - Christopher Mondy; Matias Enz; Daniel Rust (Transportation Research Interdisciplinary Perspectives)
Autonomous semi-trucks are poised to be a disruptive technology in the motor carrier industry, and many studies extol the virtues of autonomous vehicles. The benefits cited in these studies generally assume high market penetration rates, yet there is a lack of rigorous qualitative studies that investigate the factors that will drive autonomous truck adoption in the commercial transportation sector. This study describes a conceptual model featuring twelve factors that may affect autonomous truck adoption. These factors were identified from a grounded theory analysis of semi-structured interviews with a sample of transportation professionals from different companies, positions, and geographic regions within the United States. The results shed light on what might spur adoption of autonomous technologies in the motor carrier industry and provide information that can guide the development of new technologies, procedures, and regulations.